1989
DOI: 10.1139/g89-123
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the small heat shock genes during Drosophila development: comparison of the accumulation of hsp23 and hsp27 mRNAs and polypeptides

Abstract: Seven heat shock genes are clustered within 15 kilobases of DNA at the Drosophila melanogaster chromosomal site 67B. They show a complex pattern of expression in the absence of external stress during normal development of this organism. In this paper, we quantitatively compare the abundance of the messenger RNAs for these seven genes at all major stages of Drosophila development and then focus on hsp23 and hsp27 for which available antibodies allow the comparison between the accumulation of the mRNAs and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
4

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
(64 reference statements)
4
18
0
4
Order By: Relevance
“…The above differences in the expression of the medfly and Drosophila hsp27 genes, may suggest differential regulation of the hsp27 gene in the two species during their embryonic and early larval development. During prepupal, pupal and adult male and female development, the expression pattern of the hsp27 gene in medfly was found very similar to the respective pattern in Drosophila (Mason et al ., 1984; Pauli et al ., 1989). In agreement with several reports in Drosophila (Pauli et al ., 1990; Marin & Tanguay, 1996; Michaud et al ., 1997b), significant amounts of hsp27 RNA were found in both ovaries and testis of mature medflies suggesting specific functions during oogenesis and spermatogenesis.…”
Section: Discussionsupporting
confidence: 94%
“…The above differences in the expression of the medfly and Drosophila hsp27 genes, may suggest differential regulation of the hsp27 gene in the two species during their embryonic and early larval development. During prepupal, pupal and adult male and female development, the expression pattern of the hsp27 gene in medfly was found very similar to the respective pattern in Drosophila (Mason et al ., 1984; Pauli et al ., 1989). In agreement with several reports in Drosophila (Pauli et al ., 1990; Marin & Tanguay, 1996; Michaud et al ., 1997b), significant amounts of hsp27 RNA were found in both ovaries and testis of mature medflies suggesting specific functions during oogenesis and spermatogenesis.…”
Section: Discussionsupporting
confidence: 94%
“…RNase protection and RT-PCR analyses revealed that heat shock-induced accumulation of HSP30A and C was first detectable at the early tailbud stage of development, whereas HSP30D mRNA was not heat-inducible until the midtailbud stage [Krone and Heikkila, 1989;Ali et al, 1993;Ohan and Heikkila, 19951. Other examples of differential expression of gene families during Xenopus development have been reported, including actin [Mohun et al, 19831, activin [Thomsen et al, 19901, insulin [Shuldiner et al, 19911, bone morphogenetic protein (Suzuki et al, 1993), and integrin [Whittaker and DeSimone, 19931. In Drosophila, the small HSPs display a very complex temporal and spatial pattern of gene expression during development [Sirotkin and Davidson, 1982;Cheney and Shearn, 1983;Zimmerman et al, 1983;Ayme and Tissieres, 1985;Glaser et al, 1986;Arrigo and Pauli, 1988;Pauli et al, 1989Pauli et al, , 1990Marin et al, 19931. For example, both HSP27 and HSP23 show tissue-specific expression during development with HSP27 being localized to the central nervous system, gonads and imaginal discs at the pupal stage, and HSP23 being constitutively expressed in the imaginal wing discs [Cheney and Shearn, 1983, Pauli et al, 19901.…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila encodes genes for at least four α-Crystallin-related proteins: hsp22, hsp23, hsp26 and hsp27 (Ingolia and Craig 1982). Hsp23 is specifically upregulated in adult CCs under heat-stress conditions (Marin et al 1996), and is likely to be expressed in CCs and PPCs during late pupation (Pauli et al 1989), but whether any of the putative α-Crystallin proteins are expressed in the normal adult corneal lens is unknown. Another protein reported as being expressed in the fly corneal lens, called Retinin, is produced in photoreceptors, requires Eya for its expression, and is secreted into the corneal lens (Kim et al 2008).…”
Section: Drosophila Compound Eye Development: An Overviewmentioning
confidence: 99%